Developmental life stages of the Pickersgill's reed frog (Hyperolius pickersgilli) in an ex‐situ environment at Johannesburg Zoo's captive breeding facility, South Africa. Issue 6 (7th March 2022) - du Plessis, Ian; Armstrong, Adrian; Malepa, Piet L.; Kanengoni, Arnold T.; Price, Cormac; Downs, Colleen T.
Abstract: Globally, the threats of habitat loss and disease on amphibian survival have necessitated the creation of ex‐situ insurance populations as a conservation tool. We initiated a captive breeding project to create an insurance population for the endangered Pickersgill's reed frog ( Hyperolius pickersgilli Raw, 1982) at the Johannesburg Zoo from parents collected from KwaZulu‐Natal Province, South Africa, in 2017. We found that this species has seven developmental life stages, each with unique management requirements. The quiescent tadpoles hatched 6–8 days after the eggs were laid and remained at this stage for 2 days. The next stage, the developing tadpoles, showed no form of cannibalism or carrion feeding. The external appearance of the first leg (the right hind) occurred 5–6 weeks after the tadpoles hatched, and the metamorph stage was reached after 7–8 weeks. The metamorph stage lasted 3–5 days, after which tail resorption was complete and the froglet stage reached. Froglets could not be sexed externally, although body color changed based on the amount of light present at the resting place. Sub‐adults were 6 months and older with adult coloration and sex differentiation visible even with color change. Adults were older than 18 months and fully developed and sexually mature, displaying amplexus, oviposition, and external fertilization. A greater understanding of Pickersgill's reed frog's developmental stages and physiological and environmental needs can improve captive breeding and subsequent release of the frogs, facilitate captive breeding elsewhere, and improve the species' conservation status. Abstract : Stages of tadpole development from Week 1 to Week 8 in Pickersgill's reed frogs bred in captivity at Johannesburg Zoo, South Africa. Research highlights: Successful captive breeding of Pickersgill's reed frog ( Hyperolius pickersgilli ) at the Johannesburg Zoo from parent specimens collected from KwaZulu‐Natal Province, South Africa. Discovery of seven distinct life stages for the species with unique requirements at each stage. The development of the frog from the egg to metamorph took 8 weeks.